UJI COBA MODEL âMYâ TERHADAP KETERAMPILAN KLINIS PENJAHITAN PERINEUM DERAJAT DUA - Fathunikmah, Fathunikmah; Rafida, Rafida (Asosiasi Pendidikan Kebidanan Indonesia, 2018)
Good clinical skills should be preceded by good skills-lab as well. Therefore, before being used for practice in the treatment room, teaching aids should be used repeatedly so that health workers can master the desired competencies. The purpose of this research was to determine the effectiveness and efficiency of perineal repair model to the clinical skill learning of second degree perineum repair at Camar Room I and II of Arifin Achmad Hospital of Pekanbaru in 2017. This qualitative used a phenomenological design. The research was conducted from February to July 2017. The informants in this research were all midwives who worked in the study site amounted to 20 people. Data were collected by FGD method. The result of the research was that this model was quite realistic when grafted with pelvic model. As a second-grade perineal wound repair material, this model can also be categorized as realistic because it could be sewn on 1 cm of wound peaks, bleary, and subcuticular. The durability of this model was reviewed as low-cost with its good durability and safety.